2022
DOI: 10.3390/jcm11226703
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Still’s Disease: A Comparative Analysis of Phenotypic Forms in a Cohort of 238 Patients

Abstract: Still’s disease (SD) is a heterogeneous autoinflammatory disorder for which several phenotypes have been described. We conducted a retrospective study to re-evaluate the dichotomous view of the disease, to compare the juvenile and adult forms, and to look for prognostic factors. We collected data from ten French centers, seeking patients with a diagnosis of adult-onset SD (AOSD) or systemic juvenile idiopathic arthritis (sJIA). We identified 238 patients, 152 (64%) of whom had AOSD while 86 (36%) had sJIA. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“… 26 Actually, our clinical findings are similar to that reported by Neau et al , who identified a similar clinical presentation between paediatric and adult groups, except for sore throat and myalgia, which were more frequent in adults in their study. 27 Neau et al 27 identified a statistically significant difference between paediatric and adult-onset groups in the CRP and serum ferritin levels. In this regard, ferritin levels have been distinguished between adult and elderly cases in our non-paediatric patients, probably affecting the difference between paediatric and adult groups.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Actually, our clinical findings are similar to that reported by Neau et al , who identified a similar clinical presentation between paediatric and adult groups, except for sore throat and myalgia, which were more frequent in adults in their study. 27 Neau et al 27 identified a statistically significant difference between paediatric and adult-onset groups in the CRP and serum ferritin levels. In this regard, ferritin levels have been distinguished between adult and elderly cases in our non-paediatric patients, probably affecting the difference between paediatric and adult groups.…”
Section: Discussionmentioning
confidence: 99%
“…Among the JIA subtypes, systemic onset JIA (sJIA) is more likely to have pericardial effusion [ 105 ]. Recent data suggests pericarditis is present in 7.2% to 28% children with sJIA [ 106 , 107 ] and cardiac tamponade in 2.5% [ 108 ]. There is no difference in cardiac involvement among different subgroups of sJIA, with pericarditis seen in 19% of systemic subtype of sJIA and 15.4% in chronic course of sJIA [ 108 ].…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…Symptomatic myocarditis is seen in 3.5% of children with JIA [ 104 ]. More recent series have shown myocarditis to be complicate sJIA in 4.2% [ 108 ]. Echocardiographic evidence of subclinical myocarditis is seen in 10% in children with sJIA [ 104 ].…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 99%
See 1 more Smart Citation